DOP56 Long-term disease progression and resective surgery rates in Crohn's disease over different therapeutic eras – a population-based study from western Hungary between 1977–2020, data from the Veszprem county cohort. (30th January 2023) - Gonczi, L; Lakatos, L; Golovics, P A; Pandur, T; David, G; Erdélyi, Z; Szita, I; Lakatos, P L
Abstract: Background: Few population-based studies have investigated the long-term surgery rates of Crohn's disease (CD). The present study is a continuation of the Veszprem IBD population based cohort with a follow-up since 1977. Our aim was to analyze the long-term disease course and surgery rates over different therapeutic eras in a prospective population-based database from Veszprem Province, including incident CD patients. Methods: Patient inclusion was between January 1, 1977 and December 31, 2018; follow-up ended December 31, 2020. Both in-hospital and outpatient records were collected and comprehensively reviewed at diagnosis and during clinical follow-up. Surgery rates were examined in three different eras based on time of diagnosis: cohort-A, 1977-1995; cohort-B, 1996-2008; and cohort-C, 2009-2018. Results: Data of 946 incident CD patients were analyzed (male/female: 496/450; median age at diagnosis:28 years(y) [IQR: 22-40]), with a median of 15y(IQR 9-21) follow-up. Table 1. Overall immunosuppressive therapy use was increasing by time (48.0%/62.4%/65.5%), as well as the probability of biological therapy initiation within 5 years of diagnosis (0.0±0%/7.3±1.2%/22.7±2.2%) in cohorts A/B/C. Figure 1 . The cumulative probability of disease behavior progression in patients with luminal (B1) behavior into stenosing or penetrating phenotype (B2/B3) was 27.1±5.3%/ 21.5±2.5%/ 11.3±2.2% in cohorts A/B/C after 5 years (pLogRank<0.001). Figure 2. The cumulative probability of resective surgery in the total population was 34.2±1.6% after 10 years, 44.9±2.0% after 20 years, and 61.9±4.2% after 30 years. The cumulative probability of first resective surgery between cohorts A/B/C were as follows: 28.7±3.7%/ 26.3±2.1%/ 28.1±2.4% after 5 years; 39.4±4.0%/ 32.6±2.2%/ 33.0±2.7% after 10 years; and 54.5±4.1%/ 41.4±2.6% (cohorts A/B) after 20 years. There were no statistically significant differences in surgery rates between the cohorts overall [pLogRank=0.055], however a notable decrease in long-term (20y) surgery rates was observed comparing cohorts B and C vs. cohort A. Figure 3. A cox-regression multivariate analysis showed that stenosing or penetrating disease (B2/B3) behavior (HR 4.52; 95%CI 3.60-5.68; p<0.001) and ileal (L1) location at diagnosis (HR 1.30; 95%CI 1.05-1.61; p=0.016) were independent predictors of resective surgery. Table 2. Conclusion: Disease behavior progression decreased, however no differences in resective surgery risk at 5 and 10 years from diagnosis have been observed in incident CD patients despite the increasing use of immunosuppressives and biologicals in this population based cohort. However, a decrease is shown in long term (20y) surgery risk comparing the earliest cohort to latter ones with higher immunosuppressive and biological use.